Pengaruh Social Media Celebrity terhadap Perilaku Pembelian Impulsif di E Commerce dengan Attitude Toward Online Impulse Buying sebagai Mediator pada Generasi Z Digital Native - Muhammad Wildan Khoirul Muna; Muhammad Hamdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examines the influence of social media celebrities on online impulse buying behavior with attitude toward online impulse buying as a mediating variable among Generation Z digital natives in Indonesia. The study uses a quantitative approach with an explanatory design. Data were collected through an online survey of 177 Generation Z respondents who actively use social media and e-commerce. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that social media celebrities have a positive and significant effect on attitudes toward online impulse buying and online impulse buying behavior. In addition, attitudes toward online impulse buying have a significant effect on online impulse buying behavior and partially mediate the relationship between social media celebrities and online impulse buying behavior. These findings indicate that the influence of influencers is not only emotional but also shapes consumers' evaluative attitudes toward impulsive buying. Theoretically, this study expands the application of the Stimulus Organism Response (SOR) framework by placing attitude as an internal cognitive mechanism. Practically, the results of this study have implications for digital marketers in designing more effective influencer endorsement strategies.